Padma Bridge Rail Link Project with Special Emphasis on Padma Multipurpose Bridge, its Technological Uniqueness (MIST International Journal of Science and Technology, 2022)
The South and Southwestern part of the country is devoid of direct communication with the central part of Bangladesh due to the presence of the most important tributaries of Lower Ganges i.e. Padma River. To establish direct communication with those areas Government of Bangladesh Constructed Padma Multipurpose Bridge with the provision of road and rail traffic at the upper and lower deck of the bridge respectively. The Padma Bridge Rail Link Project (PBRLP) is the main passage connecting the East and the West of Bangladesh and is also a part of the Bangladesh-China-India-Myanmar corridor. This line is a single-track passenger-freight railway with a total length of 168.6 km. For the first time in Bangladesh, State of the Art technology ballast less tracks in Padma Bridge, its approach to viaducts and other viaducts are being adopted for providing a smooth operation for both freight and passenger traffic. Precast and prestressed long sleeper embedded in cast in-situ track slab ensures a maintenance-free track system for the railway. PBRLP, once completed will restore the missing link with the Trans-Asian railway and will provide a platform for connecting with the Dedicated Freight Corridor (DFC) of India in future. It will also contribute to the Gross Domestic Product (GDP) of the country by 1.0%.MIJST, Vol. 10, November 2022 (Special Issue: Padma Bridge): 79-84